Gharar and mispricing of equity warrants, Malaysian evidence - Haron, Razali (2014)
In Islamic finance, the use of derivatives seems to be in dispute among the scholars despites its prominent emergence in the market. Majority of scholars object the use of derivatives on the basis that it contains the element of gharar. The Jeddah Fiqh of Academy rules that options are objectionable for they could not infer options in the world today with any of the Shariah nominated options contracts. Nevertheless, some scholars argue the validity of this instrument based on the concept of khiyar-al-shart and drew parallel with the concept of bai-al urbun. This study investigates warrants pricing of 73 Malaysian warrants traded within the six year period by employing the BSOPM. There seems to be deviations of pricing where 96% (70 out of 73) of the warrants traded are mispriced in reference with their theoretical values. This mispricing of warrants indicated inefficiency in the Malaysian warrants market. Therefore, based on the argument above and the extent of mispricing revealed in the analysis, this study found the element of gharar in warrants contract when viewed from the pricing inefficiency in the market. Mispricing of warrants in Malaysian market indicates speculative activities and speculation is not allowed in Islam. Speculation may contain gharar (uncertainty) and maysir (gambling) which are all prohibited in Islam. Islam forbids these because they may result in wealth accumulation at the expense of other parties. This activity violates the concept of adl (justice), does not serve the concept of maslahah (public interest) and does not follow the maqasid al Shariah.